2011
DOI: 10.1073/pnas.1112503108
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between spontaneous and induced brain activity during human non-rapid eye movement sleep

Abstract: Humans are less responsive to the surrounding environment during sleep. However, the extent to which the human brain responds to external stimuli during sleep is uncertain. We used simultaneous EEG and functional MRI to characterize brain responses to tones during wakefulness and non-rapid eye movement (NREM) sleep. Sounds during wakefulness elicited responses in the thalamus and primary auditory cortex. These responses persisted in NREM sleep, except throughout spindles, during which they became less consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
134
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(157 citation statements)
references
References 34 publications
14
134
0
1
Order By: Relevance
“…2 and 4). These early activations in primary auditory areas are in line with other studies demonstrating activation of auditory cortices during sleep (6,7,9,10,12). Animal studies suggest that the burst firing mode of the thalamus during sleep, with its alternating on and off states, may be as effective as the tonic mode characteristic of wakefulness in relaying incoming sensory information to the cortex (41).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…2 and 4). These early activations in primary auditory areas are in line with other studies demonstrating activation of auditory cortices during sleep (6,7,9,10,12). Animal studies suggest that the burst firing mode of the thalamus during sleep, with its alternating on and off states, may be as effective as the tonic mode characteristic of wakefulness in relaying incoming sensory information to the cortex (41).…”
Section: Discussionsupporting
confidence: 76%
“…Alternatively, it has been proposed that sleep may induce a loss of integration at a late stage of cortical processing (3)(4)(5). Indeed, preserved activation of primary sensory cortices has been reported in electrophysiological studies in animals (6)(7)(8)(9) and in neuroimaging studies in humans (10)(11)(12). Furthermore, stimuli that have behavioral relevance, such as hearing one's name, may induce a broad spread of activation into higher cortical areas (10) and evoke late scalp event-related potentials (ERPs) (13).…”
mentioning
confidence: 99%
“…The sleep-protecting function of sleep spindles is supported by a number of EEG and neuroimaging studies in humans; for example, brain responses to auditory stimulus are significantly reduced when a tone is delivered concurrently with sleep spindles (31). Other studies have demonstrated a positive correlation between SD and the duration or stability of sleep (12,17), suggesting that the amount of sleep spindles might signify the strength of the gatekeeping mechanism that the thalamus exerts during sleep.…”
Section: Discussionmentioning
confidence: 75%
“…Importantly, we do not claim that NREM sleep is associated with a total obliteration of conscious mental representations. The brain remains responsive to external stimuli during NREM sleep (12,13) and dreams have been reported after NREM sleep awakenings (14). However, the aim of the current paper was not to characterize the neural correlates of these mental representations but rather to contrast brain function during normal wakefulness to that observed during a state of impoverished conscious content such as NREM sleep.…”
Section: Discussionmentioning
confidence: 97%